Rethinking the MBA : business education at a crossroads - Datar, Srikant M. (Harvard Business Press, 2010)
This book provides case studies showing how leading MBA programs have begun reinventing themselves for the better. Also offer concrete ideas for how business schools can surmount the challenges that come with reinvention, including securing faculty with new skills and experimenting with new pedagogies. Rich with examples and thoroughly researched, this book also helps to reveals why and how business schools must define a better pathway for the future.